Answer:
Step-by-step explanation:
[tex]S = \frac{n}{2} (a+l)\\2s = n(a+l)\\2s = na +nl\\\frac{2s}{a+l} = n+n\\2n = \frac{2s}{a+l}\\n = (\frac{2s}{a+l})/2\\n = \frac{2s}{2a+2l}[/tex]
To Make n subject of the formula
Step 1
: Cross multiply
Step 2 :
Use n to open the bracket
Step 3 :
Divide both sides by a +l to make n on one side of the equation
Step 4 :
Evaluate n+n = 2n
Divide both sides of the equation by 2
To make l the subject of the formula ,
Step 1 : cross multiply
Step 2 :
Use n to open the bracket
Step 3 :
Move na to the other side of the equation to isolate l
Step 4 : Divide both sides of the equation by n
[tex]S = \frac{n}{2} (a+l)\\2s = n(a+l)\\2s = na +nl\\\\2s - na = nl\\l = \frac{2s-na}{n} \\[/tex]